1H, 13C, and 15N chemical shift assignments of the phosphotyrosine binding domain 2 (PTB2) of human FE65 - Dietl, Andreas; Wild, Klemens; Simon, Bernd (Biomolecular NMR assignments, 2014)
Phosphotyrosine binding domains (PTB) are protein-protein interaction domains that play important roles in various cellular signal transduction pathways. The second phosphotyrosine binding domain (PTB2) of the human scaffolding protein FE65 interacts with the C-terminal part of the Amyloid Precursor Protein (APP) involved in Alzheimer’s disease. The structure of PTB2 in complex with a 32 amino acid fragment of APP has been solved previously by X-ray crystallography. Here, we report the NMR spectral assignments of the free FE65 PTB2. This provides the basis for further investigation of the interactions of PTB2 with peptides and small organic ligands with the aim of disrupting the PTB2-APP interaction.